Optimizing the Transportation Routes of Automotive Parts: A Case Study Sample Company - อักษรธรรม, สมจินต์; มีนคร, สมศักดิ์; พรงาม, นิรดา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to reduce the time and distance in vehicle transportation. From analyzing the problem using a fishbone diagram, it was found that the issue arises from inefficient prioritization in vehicle queue entry. Therefore, the researcher proposes route optimization to reduce travel time and distance. The study employs Route XL and Google Maps software. The results of optimizing vehicle transportation routes using Route XL in conjunction with Google Maps show that the original distance of 282.9 kilometers was reduced to 245.9 kilometers, achieving a reduction of 37 kilometers (13%). Regarding travel time, the original duration of 18 hours and 24 minutes was reduced to 17 hours and 27 minutes, representing a 5% decrease from the original travel time